Task-dependent plasticity in distributed neural circuits after transcranial direct current stimulation of the human motor cortex: A proof-of-concept study - Hodkinson, Duncan J.; Jackson, Stephen R.; Jung, JeYoung (Frontiers in Pain Research, 2022)
The ability of non-invasive brain stimulation to induce neuroplasticity and cause long-lasting functional changes is of considerable interest for the reversal of chronic pain and disability. Stimulation of the primary motor cortex (M1) has provided some of the most encouraging after-effects for therapeutic purposes, but little is known about its underlying mechanisms. In this study we combined transcranial Direct Current Stimulation (tDCS) and fMRI to measure changes in task-specific activity and interregional functional connectivity between M1 and the whole brain. Using a randomized counterbalanced sham-controlled design, we applied anodal and cathodal tDCS stimulation over the left M1. In agreement with previous studies, we demonstrate that tDCS applied to the target region induces task-specific facilitation of local brain activity after anodal tDCS, with the stimulation effects having a negative relationship to the resting motor threshold. Beyond the local effects, tDCS also induced changes in multiple downstream regions distinct from the motor system that may be important for therapeutic efficacy, including the operculo-insular and cingulate cortex. These results offer opportunities to improve outcomes of tDCS for the individual patient based on the degree of presumed neuroplasticity. Further research is still warranted to address the optimal stimulation targets and parameters for those with disease-specific symptoms of chronic pain.